Sanitasi Lingkungan di Kawasan Permukiman Tempat Pembuangan Akhir (TPA) Air ingin Kecamatan Koto Tangah Kota Padang - Ibnu Rifki; Sari Nova (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine water quality levels based on the parameters of dissolved oxygen (DO), total dissolved solids (TDS), conductivity, pH, temperature, salinity and turbidity; to assess environmental sanitation conditions; and to examine community behaviour regarding domestic waste management and environmental sanitation in residential areas surrounding the Air Dingin Final Disposal Site (TPA) in Koto Tangah Sub-district, Padang City. This study employed a quantitative descriptive method. Total sampling was used as the sampling technique. Data collection was carried out through observation, documentation, questionnaires and laboratory water quality tests. The data were analysed using Inverse Distance Weighting (IDW) and descriptive statistics in the form of percentages to describe environmental sanitation conditions, water quality and community behaviour regarding domestic waste management. The results of the water quality tests showed that the parameters of TDS, temperature, salinity, conductivity and turbidity met the clean water quality standards, whilst the pH and DO parameters in some samples did not yet meet the relevant standards. Meanwhile, environmental sanitation conditions in the residential areas surrounding the Air Dingin Landfill were classified as good, with an index value of 78.87 per cent. The clean water facilities component scored 79.62 per cent and waste management 76.85 per cent, which fall into the ‘good’ category, whilst household latrine facilities at 89.58 per cent and waste disposal facilities at 94.44 per cent fall into the ‘very good’ category.